2017
DOI: 10.1038/s41598-017-07515-y
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns and drivers of daily bed-level dynamics on two tidal flats with contrasting wave exposure

Abstract: Short-term bed-level dynamics has been identified as one of the main factors affecting biota establishment or retreat on tidal flats. However, due to a lack of proper instruments and intensive labour involved, the pattern and drivers of daily bed-level dynamics are largely unexplored in a spatiotemporal context. In this study, 12 newly-developed automatic bed-level sensors were deployed for nearly 15 months on two tidal flats with contrasting wave exposure, proving an unique dataset of daily bed-level changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 52 publications
5
44
1
Order By: Relevance
“…Zuidgors did not result in sufficient bed level heights after conversion. However, the obtained bed level changes were comparable with studies wherein similar measurements were conducted (e.g., Hu et al, ; Lawler, ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Zuidgors did not result in sufficient bed level heights after conversion. However, the obtained bed level changes were comparable with studies wherein similar measurements were conducted (e.g., Hu et al, ; Lawler, ).…”
Section: Discussionsupporting
confidence: 86%
“…This confirms the findings of earlier studies having spatial data on short-term bed level dynamics (e.g., Bouma et al, 2016;. It furthermore agrees with long-term studies (multiple years) that also showed increasing bed level dynamics over the tidal flat toward the sea (e.g., Andersen et al, 2006;Hu et al, 2017;O'Brien et al, 2000). The previously mentioned studies were extended by the present study with measurements at the transition from tidal flat to marsh, resulting in observations both on the vegetated marsh and tidal flat.…”
Section: Toward Understanding Spatial and Temporal Patterns In Short-supporting
confidence: 91%
See 1 more Smart Citation
“…Deloffre et al (2005) concluded that tidal forcing was also the dominant driving force responsible for the erosion of a mudflat located in the upper macrotidal Seine estuary, France. This characteristic time-scale is also present in the variation of τc as well as τ tot during storm events, which was significantly correlated to bed-level dynamics at Zuidgors and Baarland (Hu et al 2017). Yet, contrary to Hu et al (2017) tidal forcing cannot explain variation in long-term bed level dynamics along the Galgeschoor.…”
Section: Discussionmentioning
confidence: 69%
“…This characteristic time-scale is also present in the variation of τc as well as τ tot during storm events, which was significantly correlated to bed-level dynamics at Zuidgors and Baarland (Hu et al 2017). Yet, contrary to Hu et al (2017) tidal forcing cannot explain variation in long-term bed level dynamics along the Galgeschoor. Spatial variations in sediment characteristics (mud content, particle size, Figure 3.16) interact with tidal forcing in shaping elevation changes at the high plot of GSc2 over the long-term, and possibly other factors may be at work.…”
Section: Discussionmentioning
confidence: 69%